Language Awareness Among Undergraduate Sports Sciences Students - Ayse Demir,; Ezgi Inal, (Journal of Educational Issues, 2024)
The ability of individuals to feel part of their culture highly depends on the extent to which they can use their native language and how they can manage linguistic processes. In this context, regardless of occupation or age, one needs to use the language in daily communication—an element maintaining the social order—correctly and in accordance with the language-specific rules. The aim of this study was to explore language awareness among undergraduate sports sciences students. A total of 205 students enrolled at schools of sports sciences in Istanbul, 64.9% (n = 133) were males and 35.1% (n = 72) were females, voluntarily participated in the research. We collected the data using a demographic information form and the “Everyday Language Awareness Scale”. The 5-point Likert-type scale consists of 17 items within four sub-scales. While showing the frequencies of the responses to the scale items, we used an independent-samples t-test and one-way analysis of variance (ANOVA) to analyze the participants’ scores by their demographics. We calculated Cronbach’s alpha for the total score to be 0.86. Overall, we concluded that the participants had significantly higher awareness of the Turkish language by their total and subscale scores.